Dr Faustus an exploration of voice, sound and body - Contemporary Arts Media (Australia : Contemporary Arts Media, 2008)
Workshop and performance from Voice Theatre Lab, featuring recent work. The production of Dr. Faustus explores abstract imagery through voice and body, drawing inspiration from Japanese Butoh dance. The training session 5 is a filmed, staged workshop of the Voice Theatre Lab that focuses on vocal actions, energies, and the image, through depiction of the interrelationship of the 5 elements wood, fire, metal, water, and earth.
DVD format
Keywords: Movement (Acting).; Voice culture; Acting; Theatre